2020
DOI: 10.1177/1938640020921573
|View full text |Cite
|
Sign up to set email alerts
|

First Metatarsophalangeal Joint Arthrodesis Using Memory Staples: Clinical and Functional Results

Abstract: Background. We present clinical and functional results of first metatarsophalangeal joint (MTPJ) arthrodesis using Memory staples. Methods. This retrospective observational study reviewed MTPJ arthrodesis with Memory staples from 2012 to 2016. Results. The mean age of 50 patients (55 feet) was 63 years (range 41-77 years). Forty-one feet were in women. Indication was hallux rigidus (n = 49) and hallux valgus (n = 6). The overall union rate was 98.2% (n = 54 of 55), including delayed healing in 3 (5.5%). The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…As for functional outcomes, it was to synthesise the results due to vagueness in reporting, missing information, and variations in the measurement tools used. Challagundla et al [36], the only study using the staple technique, obtained the highest union rate of 98.2%, with a mean union time of 84 days. However, it has the highest complication incidence of 9.1%.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As for functional outcomes, it was to synthesise the results due to vagueness in reporting, missing information, and variations in the measurement tools used. Challagundla et al [36], the only study using the staple technique, obtained the highest union rate of 98.2%, with a mean union time of 84 days. However, it has the highest complication incidence of 9.1%.…”
Section: Discussionmentioning
confidence: 95%
“…Even though a high union rate was achieved, this review's data revealed staples as inferior to other techniques in terms of stability and ability to allow early weightbearing. It should, however, be viewed with scepticism because it is just one study with a small sample size [36]. Further studies are needed to determine the stability and effectiveness of staples for FMPJ arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were unsurprising, as a prior study showed staples provided sufficient compressive force to achieve fusion of the first MTPJ without the additional stability provided by the dorsal plating construct. 45,46 Outside of fusion rates, the operative time as well as the tourniquet time were less when the SCP alone (7 of 23) was used, in comparison with the LPP cohort where an interfragmentary screw was almost always used (17 of 21). However, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%